Ergonomic risk assessment and symptoms of musculoskeletal disorders among garment manufacturing workers in Kota Bharu, Kelantan - Khamarollah, Nurshatira; Hamzah, Nurul Ainun; Abd Rahman, Syamimi; Samsudin, Khairilmizal; Abdul Samad, Nurul Izzah; Md Yasir, Ahmad Shah Hizam; Mohd Tamrin, Shamsul Bahri (Korean Institute of Industrial Engineers, 2024)
The garment manufacturing industry is a labor-intensive work that is often considered a safe working place. A significant physical and health risks associated with this industry, such as Musculoskeletal Disorders. These risks can accumulate over time and lead to serious health problems. A cross-sectional study was conducted to assess the ergonomic risk and symptoms of MSDs among 154 workers. Symptoms of MSDs were assessed using the Cornell Musculoskeletal Discomfort Questionnaire and the ergonomic risks were assessed using the Rapid Upper Limb Assessment (RULA). The ergonomic risks were 49.3% high, 48.0% medium and 2.6% low. Wrist was the worst affected body region, while the predominant body regions for symptoms of MSDs were the right shoulder, neck, left shoulder, and lower back. The highest risk factors for MSDs were prolonged working in the same position and doing repetitive movements of the arms and hands. There was a significant correlation between the RULA score and the symptoms score of MSDs at each body region (p<0.01). In addition, a significant association was found between demographic factors (years of employment, marital status, and age) with scores of several body regions (lower back, hip/buttocks, right and left knee) (p<0.05). In conclusion, significant ergonomic risks and MSDs among garments were found among garment workers. Therefore, control measures should be taken by the administration to minimize the risks of MSDs.